SOUTHEAST ASIA REGIONAL COOPERATION ON TACKLING MARINE PLASTIC LITTER - Febryani Sabatira (Faculty of Law Universitas Lampung, 2020)
The sea covers 70% of the earth and is the source of livelihood for people all over the world. It is estimated that each year 6-12 million tons of plastic are dumped into the ocean. In the Southeast Asian region, the concentration of marine plastic litter in the ocean has reached a severe level. Six out of the 10 ASEAN countries are listed on the Top 20 of countries ranked by mass of the mismanaged plastic waste. Various legal instruments and supporting programs have been developed. However, the existence of these instruments and programs have not had a significant impact on combating marine plastic litter. This study aims to find out how a regional community can conquer the severe pollution of our oceans. This research uses normative legal analysis with secondary data sources and literature study techniques. The result of the research showed ASEAN initiated the regional cooperation amongst southeast Asia states in combating marine plastic litters as the competent regional organisation that carried out through institutional frameworks and subsidiary working groups, which have enacted two regional soft-law instruments, namely the Bangkok Declaration on Marine Debris and the ASEAN Framework for Action on Marine Debris.